Design and evaluation of a three‐dimensional virtual laboratory on vector operations. Issue 3 (3rd March 2019) - Salinas, Isabel; Giménez, Marcos H.; Cuenca‐Gotor, Vanesa P.; Seiz‐Ortiz, Rafael; Monsoriu, Juan A.
Abstract: In Physics, many quantities are vectors, and their use requires typical operations such as addition, subtraction, scalar multiplication, scalar product (dot product), vector product (cross product), and scalar triple product. This is a very basic topic in all General Physics courses for Engineering degrees. However, we have detected that some students lack a deep understanding of vector operations and their properties. In this study, we present a virtual laboratory (developed using the tool "Easy Java Simulations") for the study and understanding of these topics. The user can introduce the components of the input vectors and gets a three‐dimensional representation, which can be scaled and rotated for better visualization. Any of the aforementioned operations can be selected, and the result is shown both numerically and graphically. The user can also modify any represented vector. In this way, the virtual lab provides a real‐time visualization of how the change affects the result. The possibility of limiting the changes to either magnitude or direction is also included. The efficiency of the virtual laboratory has been tested analyzing the results obtained in two groups of students (virtual laboratory vs traditional resources). A satisfaction survey has been also carried out.